Rapid Assessment of Health Services in Punjab using a Mixed Method Approach - Kumar, Rajesh; Tripathy, Jaya Prasad; Singh, Navpreet; Kaur, Manmeet; Prinja, Shankar; Lakshmi, PVM; Gupta, Mamta; K, Madhanraj; Bhattacharya, Sudip (Indian Journal of Community Health, 2015)
Introduction: The out-of-pocket expenditure is quite high in Punjab. Hence, a rapid review of health facilities was undertaken to suggest remedial measures. Methods: Mixed method research approach was used to identify strengths and weaknesses of the health services in Punjab. All health institutions were included in the assessment from the three purposively sampled districts – one from each of the three regions of Punjab. Tools were developed to collect data from record review, observations, and in-depth interviews. Six building blocks framework proposed by the World Health Organization was used for data collection and analyses. Results: In general physical infrastructure, especially the buildings were found to be reasonably constructed at most of the healthcare facilities. However, the maintenance was not regular. The vacancies for general doctors, specialist doctors, nurses, and paramedics were 26%, 38%, 31% and 12% respectively. Supply of drugs was irregular and inadequate. A large proportion (45%) of ‘user charges’ were spent on purchase of drugs and other consumables. Most registers were found to be updated, and reports were transmitted to higher levels usually on time. However, institutionalized system of monitoring and supervision was lacking. Govt. hospitals were providing in-patient care to about 35.5% of those who were estimated to need hospitalization. State had allocated about Rs. 1200 crores to health (0.46% of GDP), thus, spending only Rs. 433 per capita per year. Conclusions: Despite constraints, the government health service is catering to the needs of a large section of the population. Rapid health system assessment at periodic intervals using a mixed method approach can supplement routine monitoring of the health system.